Ambienti digitali per lo sviluppo delle competenze trasversali nella didattica universitaria - Concetta La Rocca; Massimo Margottini; Rosa Capobianco (LED Edizioni Universitarie, 2014)
Digital Environments for the Development of Transversal Competences in University Education International studies show that university teaching is making increasing use of digital environments to integrate traditional teaching. In this paper we consider the contribution that can be made by online environments to develop students' positive and proactive attitudes with respect to the academic curriculum in order to reduce student drop-out, encourage greater regularity in their academic career, develop transversal competences and promote student guidance. In particular, we have observed the online activities in academic year 2013/2014 carried on by students of General Didactics, a degree course in the Department of Educational Sciences of «Roma Tre» University. These activities include the realization of two online practical classes: completion of the QSA (Questionnaire for Learning Strategies); participation in a cooperative online learning exercise. In both experiences we analyzed the procedures and outcomes. We observed that, through the QSA, students reflected on their learning strategies and on the importance of planning their university commitments: a positive factor is the high percentage of students who took the exam successfully in the first session (approximately 68%). In addition, the questionnaire data clearly show that students found that group work helps to develop cognitive and meta-cognitive competences as well as relationship competences. In particular, we found that in the General Didactics examination the students who had experienced cooperative learning obtained higher grades, on average, than those who did not, and that the former group had less «sigma» compared to the latter.